'People like you?': how people with hypertension make sense of future cardiovascular risk—a qualitative study. Issue 11 (8th November 2018) - Marshall, Iain J; Wolfe, Charles D A; McKevitt, Christopher
Abstract : Objectives: Cardiovascular disease (CVD) prevention guidelines recommend that patients' future CVD risk (as a percentage) is estimated and used to inform shared treatment decisions. We sought to understand the perspectives of patients with hypertension on their future risk of CVD. Design: Qualitative, semistructured interviews and thematic analysis. Participants: People with hypertension who had not experienced a cardiovascular event recruited from primary care. Setting: Participants were purposively sampled from two primary care practices in South London. Interviews were transcribed, and a thematic analysis was conducted. Results: 24 people participated; participants were diverse in age, sex, ethnicity and socioeconomic status. Younger working-aged people were under-represented. Contrasting with probabilistic risk, many participants understood future CVD as binary and unknowable. Roughly half of participants avoided contemplating future CVD risk; for some, lifestyle change and medication obviated the need to think about CVD risk. Some participants identified with one portion of the probability fraction ('I'd be one of those ones.'). Comparison with peers (typically partners, siblings and friends of a similar age, including both 'healthy' and 'unhealthy' people) was most frequently used to describe risk, both among those who engaged with and avoided risk discussion. This contrasts with current risk scores, which describe probabilities in people with similar risk factors; many participants did not identify with such a group, and hence did not find these probabilities meaningful, even where correctly understood. Conclusions: Risk as typically calculated and communicated (eg, the risk of '100 people like you') may not be meaningful for patients who do not identify with the denominator. Comparing an individual's risk with their peers could be more meaningful.